DETECTION AND MONITORING SYSTEM OF SMOKE CONCENTRATION WITH SMOKE DETECTOR AND CAMERA TRACKER - Abdullah Abdullah (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2018)
Detection and monitoring system of smoke concentration is very useful forplaces that tend to be flammable or area/room that are designated as non smoking area. This system is not only able to detect smoke but also determine the existence of point/source of smoke (areas where greater smoke concentrations are detected). The presence of smoke sources can be observed by monitoring systems with the addition of mobile camera trackers to focus on the presence of smoke sources. This system is veryhelpful to facilitate the building/room security officers in monitoring the smoke in their area, either smoke caused by fire or cigarette smoke in non smoking area. This researchuses MQ-2 type smoke sensor, ATmega32 as controller, and also equipped with LCD display, monitor screen, and camera tracker. The test results prove that the system has been successfully integrated and able to achieve the desired target, that this system can be used properly to detect and monitor the presence of smoke sources.Keywords: camera tracker, detection and monitoring system, and smoke sensor.